The contribution of international R&D to firm profitability - Bettina Peters; Anja Schmiele (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
The internationalisation of corporate R&D opens up the chances to participate in international knowledge sharing. This increasingly motivates firms to accelerate the pace and extent of their international R&D activities in order to enhance innovativeness and consequently competitiveness and profitability. Such business ventures, however, might be associated with huge organizational costs as well as risks of outgoing knowledge spillovers. In this paper we empirically address the question whether international R&D activities boost profitability. We employ a large data set of about 1300 firms from the German Community Innovation Survey (CIS). The empirical results demonstrate that R&D location matters for profitability. Firms with both domestic and foreign R&D activities make significantly higher profits than all other firms, including those that carry out solely domestic R&D. We furthermore ascertain that the degree of R&D internationalisation affects profitability. Our findings suggest that medium decentralised firms which innovate in two or three foreign countries outperform firms with centralized or highly decentralized international R&D strategies. Notwithstanding, decentralized firms achieve a higher firm performance than firms that solely conduct R&D activities in their home country.
urn:nbn:de:bsz:180-madoc-31137
Keywords: O32; F23; 330; R&D; Innovation; Internationalisation; Firm performance; Profit